2016
DOI: 10.1186/s12873-016-0100-7
|View full text |Cite
|
Sign up to set email alerts
|

Barriers in detecting elder abuse among emergency medical technicians

Abstract: Background: Elder abuse and neglect are highly under-reported in the United States. This may be partially attributed to low incidence of reporting among emergency medical technicians' (EMTs), despite state-mandated reporting of suspected elder abuse. Innovative solutions are needed to address under-reporting. The objective was to describe EMTs' experience detecting and reporting elder abuse. Methods: Qualitative data were collected from 11 EMTs and 12 Adult Protective Services (APS) caseworkers that participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 24 publications
2
15
0
6
Order By: Relevance
“…Many other states have these laws, which may impact EMS provider practice. However, similar themes were uncovered in a recent study in the state of Texas, 43 which has mandatory reporting. Although the focus of that study was somewhat different, concentrating on the interaction of emergency personnel with APS, comparable issues were raised.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Many other states have these laws, which may impact EMS provider practice. However, similar themes were uncovered in a recent study in the state of Texas, 43 which has mandatory reporting. Although the focus of that study was somewhat different, concentrating on the interaction of emergency personnel with APS, comparable issues were raised.…”
Section: Discussionsupporting
confidence: 63%
“…Although the focus of that study was somewhat different, concentrating on the interaction of emergency personnel with APS, comparable issues were raised. 43 These included very low reporting rates by EMS and barriers to reporting including limited training and time limitations. 43 Other research has also suggested that mandatory reporting laws do not affect health care provider reporting of elder mistreatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Os técnicos de emergência pré-hospitalar, em específico, sentem que têm a responsabilidade de denunciar situações suspeitas de abuso e sentem-se culpados se não o fizerem. 35 Além das restrições de tempo a que estão sujeitos, a falta de protocolos e os problemas de comunicação aquando da tentativa de denúncia são fatores que favorecem a falta de denúncia. 35 É uma grande responsabilidade moral, considerando que se poderá destruir a vida de alguém com base apenas na intuição.…”
Section: O Papel Dos Profissionais De Saúdeunclassified
“…A determinação da prevalência atual do abuso de idosos tem-se revelado uma tarefa complexa, designadamente em virtude das variadas metodologias utilizadas 4,6,9,24 e das diferentes populações estudadas. 9,35 Esta dificuldade encontra-se espelhada, por exemplo, numa revisão sistemática efe-revisões tuada em 2015 por Dong, que referia taxas de prevalência variando de 2,2 a 61,1%. 25 Diversos estudos indiciam tratar-se, efetivamente, de um problema comum.…”
unclassified